Interconnections between urolithiasis and oral health: a cross-sectional and bidirectional Mendelian randomization study - Xu, Jin-Zhou; Sun, Jian-Xuan; Miao, Lin-Tao; Zhang, Si-Han; Wang, Wen-Jie; Liu, Chen-Qian; Xia, Qi-Dong; Lu, Jun-Lin; Zhou, Peng; Lv, Yong-Man; Xun, Yang; Guan, Wei; et al. (Frontiers in Medicine, 2023)
Introduction Urolithiasis is one of the most common diseases for urologists and it is a heavy burden for stone formers and society. The theory of the oral–genitourinary axis casts novel light on the pathological process of genitourinary system diseases. Hence, we performed this study to characterize the crosstalk between oral health conditions and urolithiasis to provide evidence for prevention measures and mechanisms of stone formation. Materials and methods This population-based cross-sectional study included 86,548 Chinese individuals who had undergone a comprehensive examination in 2017. Urolithiasis was diagnosed depending on the results of ultrasonographic imaging. Logistic models were utilized to characterize the association between oral health conditions and urolithiasis. We further applied bidirectional Mendelian randomization to explore the causality between oral health conditions and urolithiasis. Results We observed that presenting caries indicated a negative correlation with the risk for urolithiasis while presenting gingivitis [OR (95% CI), 2.021 (1.866–2.187)] and impacted tooth [OR (95% CI), 1.312 (1.219–1.411)] shown to be positively associated with urolithiasis. Furthermore, we discovered that genetically predicted gingivitis was associated with a higher risk of urolithiasis [OR (95% CI), 1.174 (1.009–1.366)] and causality from urolithiasis to impacted teeth [OR(95% CI), 1.207 (1.027–1.418)] through bidirectional Mendelian randomization. Conclusion The results cast new light on the risk factor and pathogenesis of kidney stone formation and could provide novel evidence for the oral–genitourinary axis and the systematic inflammatory network. Our findings could also offer suggestions for tailored clinical prevention strategies against stone diseases.